MATRIKS SCORE DAN APLIKASINYA DALAM PENGAMANAN PESAN RAHASIA - Tomasouw, Berny Pebo; Mado, Glevi E.; Persulessy, Elvinus R. (PATTIMURA UNIVERSITY, 2018)
The exchange of general information or confidential information between two persons through a medium does not guarantee its safety. This makes the sender of information and the recipient of information needs to be vigilant. In this case, the role of data encoding is very important. One of the most commonly used and recognized data encryption is cryptography. Cryptography is a technique for encrypting data through the process of encryption and decryption process by using certain keys so as generate new data that is secret. One of the cryptography is the security of secret messages using the Score matrix. The score matrix is defined as a symmetric matrix with elements of complex number and is a diagonal matrix.